ANALYSIS OF QUASI LINEAR CONVECTIVE SYSTEM (QLCS) BASED ON DOPPLER WEATHER RADAR IN THE SOUTH SULAWESI REGION - Abubakar, Ahmad Shirat; Subaer, Subaer; Husain, Husain (Indonesian Physical Review, 2024)
This research aims to analyze the characteristics of the Quasi Linear Convective System (QLCS) based on weather radar in the South Sulawesi region, which influences extreme weather. This research is a case study that focuses on the occurrence of QLCS, which grows around the waters of the Makassar Strait and moves east towards the mainland area of South Sulawesi. The study area is limited to a radius of 200 km from the weather radar center. The data processing technique uses the Rainbow application with weather radar data input from the Hasanuddin Makassar Meteorological Station. Next, the radar data output in the form of MAX products is filtered according to the criteria of Lombardo and Colle (2010) to obtain QLCS cases. The selected QLCS cases were then analyzed for their characteristics based on spatial and temporal distribution, type of formation, propagation, and Vertical Wind Shear. The data processing results found 24 cases of QLCS in South Sulawesi with varying characteristics, where the formation location was most often in the waters of the Makassar Strait with a lifetime of around 60-90 minutes. The most common type of QLCS formation is a broken line, and the most dominant QLCS propagation is towards the east, with fast-moving speed and a strong VWS category.